KEPEMIMPINAN KEPALA SEKOLAH DI PAUD ISLAM TERPADU (STUDI MULTI SITUS DI PAUD ISLAM TERPADU AL FIRDAUD DAN PAUD ISLAM TERPADU SABILAL MUHTADIN) - Mayasari; Aslamiah; Novitawati; Noorhapizah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The future development of children is significantly influenced by the current quality of education where the early stages of intelligence, character and personality development are largely formed through education in early childhood, because the early years are a unique and valuable time in life. The implementation of early childhood education requires strong leadership from the education unit. The effectiveness of the implementation of education is a key component of the growth of an institution and it depends on the quality of the school including the level of leadership strength of the principal. A leader plays a role in accountability for policies that shape social values, life skills. The policy of the principal who becomes a leader with various knowledge and experience that a leader has. The principal's leadership strategy in forming teachers is by example, discipline, instructional leadership, and empowerment of all school residents. The example and discipline possessed by the principal will be a good example for teachers and staff to implement these values in daily activities at school (Majid, 2025). Integrated Islamic Schools (SIT) are two schools that were chosen because of the strong character of the school with various peculiarities in providing quality for the school and also the leadership in the school that is able to make the school superior in the context of Integrated Islamic PAUD schools, namely Al'Firdaus Integrated Islamic PAUD and Sabilal Muhradin Integrated Islamic PAUD where both of them provide an integrated Islamic concept based on religion and knowledge processes and the provision of a curriculum that is according to the character of each school. This research is a qualitative descriptive research. In qualitative research, it is greatly influenced by the researcher's views, thoughts, and knowledge because the data is interpreted by the researcher. In accordance with the research approach used, namely the qualitative approach, the data collection instrument is the researcher himself which is termed "the key instrument" (Sugiyono, 2019).